Can the 'Ending the HIV Epidemic' initiative transition the USA towards HIV/AIDS epidemic control?. (1st December 2020) - Zang, Xiao; Krebs, Emanuel; Mah, Cassandra; Min, Jeong E.; Marshall, Brandon D.L.; Feaster, Daniel J.; Schackman, Bruce R.; Metsch, Lisa R.; Strathdee, Steffanie A.; Behrends, Czarina N.; Nosyk, Bohdan
Abstract : N/A: Using a dynamic HIV transmission model calibrated for six USA cities, we projected HIV incidence from 2020 to 2040 and estimated whether an established UNAIDS HIV epidemic control target could be met under ideal implementation of optimal combination strategies previously defined for each city. Four of six cities (Atlanta, Baltimore, New York City and Seattle) were projected to achieve epidemic control by 2040 and we identified differences in reaching epidemic control across racial/ethnic groups.